Clinical and Sociodemographic Characteristics of Depressive Disorders in Kirkuk Governorate (Tikrit Journal of Pharmaceutical Sciences, 2023)
Depression has been recognized as a major public health evidenced by its ranking of fourth position among the global burden of diseases. The aim of the study was to determine the clinical and sociodemographic characteristics of depressive disorders in Kirkuk Governorate. 231 depressed patients included 78 male patients and 153 female patients who were attending psychiatric unit were participating in this study. Diagnosis was made according to the Diagnostic Statistical Manual of Mental disorders-IV (Text Revision) (DSM-IVTR). It was observed that a significant number of depressed patients were females 153(66%), unemployed140 (61%), come from rural area142 (61.5%). The highest rate is seen in widowed 70 (30%) and divorced 65 (28%) while the lowest rate is seen in married 40 (17%). The most frequent depression subtypes are major depression 140 (61%) followed by dysthymia 35(15%), while the lowest subtype is bipolar depression 14(6%). The frequency of depression subtypes among patients are major depression 61%, dysthymia 15%, psychotic depression9.5%, postpartum depression 8.6%, bipolar depression 6%.The sociodemographic characteristic factors are consistent with some previous finding.